Crystal structure of (E)-4-hydroxy-3-((5-phenyl-1,3,4-oxadiazol-2-yl)thio)pent-3-en-2-one, C13H12N2O3S - Zou Juan; Zhao Chen-Liang; Zhang Qi-Long; Pan Lu-Tai; He Kang (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C13H12N2O3S, monoclinic, P21/c (no. 14), a = 12.3541(8) Å, b = 14.3818(10) Å, c = 7.3757(5) Å, β = 96.471(2)°, V = 1302.12(15) Å3, Z = 4, Rgt(F) = 0.0417, wRref(F2) = 0.1080, T = 293(2) K.